OPTIMAL MANAGEMENT OF PIGMENT EPITHELIAL DETACHMENTS IN EYES WITH NEOVASCULAR AGE-RELATED MACULAR DEGENERATION. Issue 11 (November 2018) - Khanani, Arshad M.; Eichenbaum, David; Schlottmann, Patricio G.; Tuomi, Lisa; Sarraf, David
Abstract : Purpose: This review aimed to determine the optimal management of retinal pigment epithelial detachments (PEDs) in neovascular age-related macular degeneration (nAMD) based on review of available evidence in the literature. Methods: A comprehensive literature review evaluates previous retrospective and prospective studies that assessed the treatment of PEDs in nAMD. Results: Studies illustrated that anti–vascular endothelial growth factor (VEGF) therapy can be effective in eyes with PED secondary to nAMD. Similar visual outcomes are associated with different anti-VEGF treatments. Higher anti-VEGF doses may improve anatomical response, without correlation with vision improvement. Fibrovascular PEDs may be difficult to treat, but even these eyes can gain vision with anti-VEGF therapy. A retinal pigment epithelial tear may develop in 15% to 20% of eyes with PEDs after anti-VEGF therapy, especially in PEDs greater than 500 µ m to 600 µ m in height; however, vision may stabilize with continued therapy. Atrophy may complicate eyes with PED and nAMD after anti-VEGF therapy, especially in association with complete PED resolution. Conclusion: Available literature suggests that anti-VEGF therapy is safe and efficacious for PED and nAMD. Treatment should focus on vision gains rather than PED resolution because there is no apparent correlation between anatomical and functional improvement in most eyes with PED and nAMD. Abstract : A comprehensive literature search suggests that anti–vascular endothelial growth factor therapy is effective in treating eyes with pigment epithelial detachment due to neovascular age-related macular degeneration. This therapy should focus primarily on vision gains because there is no apparent correlation between anatomical and functional improvement in most eyes with pigment epithelial detachment and neovascular age-related macular degeneration.